The Influence of TikTok on the Moral Conduct of High School Students: A Case Study in MAN Purwakarta - Aufa, Muhammad Irfan (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Abstract: This study explores the impact of TikTok on the moral conduct of 12th-grade social science students at MAN Purwakarta. Using a quantitative approach, a survey was conducted among 118 students, selected through stratified random sampling, to assess the relationship between social media usage and student behavior. Data collection involved structured questionnaires, semi-structured interviews, observations, and document reviews, ensuring high ecological validity. Statistical analysis, including linear regression and hypothesis testing, revealed that TikTok use does not significantly influence student morals, accounting for only 46% of the behavioral variance. The remaining 54% is attributed to individual characteristics, family environment, and peer interactions. These findings highlight the need for a more holistic approach to moral education, emphasizing family, school, and community roles alongside responsible social media use. Limitations of this study include its cross-sectional nature and focus on a single social media platform. Future research should consider longitudinal studies and a broader scope of media platforms to understand better the complex interplay between social media and moral development. Abstrak: Penelitian ini mengeksplorasi dampak penggunaan TikTok terhadap akhlak siswa kelas XII IPS di MAN Purwakarta. Menggunakan pendekatan kuantitatif, survei dilakukan terhadap 118 siswa yang dipilih melalui teknik sampling acak berstrata untuk menilai hubungan antara penggunaan media sosial dan perilaku siswa. Pengumpulan data melibatkan kuesioner terstruktur, wawancara semi-terstruktur, observasi, dan tinjauan dokumen, sehingga memastikan validitas ekologis yang tinggi. Analisis statistik, termasuk regresi linier dan uji hipotesis, menunjukkan bahwa penggunaan TikTok tidak secara signifikan memengaruhi akhlak siswa, hanya menjelaskan 46% dari variasi perilaku mereka. Sisanya, yaitu 54%, dipengaruhi oleh faktor lain seperti karakteristik individu, lingkungan keluarga, dan interaksi dengan teman sebaya. Temuan ini menunjukkan perlunya pendekatan yang lebih holistik dalam pendidikan akhlak, dengan menekankan peran keluarga, sekolah, dan komunitas, serta penggunaan media sosial yang bertanggung jawab. Keterbatasan penelitian ini termasuk sifatnya yang cross-sectional dan fokus pada satu platform media sosial. Penelitian di masa depan sebaiknya mempertimbangkan studi longitudinal dan cakupan platform media yang lebih luas untuk memahami interaksi kompleks antara media sosial dan perkembangan akhlak.